Analysis of the Implementation of Zakat, Infaq and Alms Accounting Based on PSAK 109 in Lazismu Tasikmalaya City - Rijalul Khaer; Atep Firmansyah; Edi Wayudin (Indonesian Journal of Economic & Management Sciences, 2024)
This research is a qualitative descriptive study to analyze the accounting practices of zakat, infaq and alms in Lazismu, Tasikmalaya City. The data collection method for this research is field research through interviews, observation and literature study. Interviews were conducted with the leadership and finance department of Lazismu. The results of this research indicate that not all points of PSAK 109 have been implemented by Lazismu Tasikmalaya City. The discrepancy is in the recognition of infaq and non-cash alms, namely that amil funds are separated when the muzaki determines the mustahik and distributes related accounting policies in the notes to the financial statements